CUL4B Upregulates RUNX2 to Promote the Osteogenic Differentiation of Human Periodontal Ligament Stem Cells by Epigenetically Repressing the Expression of miR-320c and miR-372/373-3p - Mi, Jun; Wang, Shuangshuang; Liu, Panpan; Liu, Chang; Zhuang, Dexuan; Leng, Xue; Zhang, Qun; Bai, Fuxiang; Feng, Qiang; Wu, Xunwei (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) within the periodontal ligament (PDL), termed periodontal ligament stem cells (PDLSCs), have a self-renewing capability and a multidirectional differentiation potential. The molecular mechanisms that regulate multidirectional differentiation, such as the osteogenic differentiation of PDLSCs, remain to be elucidated. Cullin 4B (CUL4B), which assembles the CUL4B-RING ubiquitin ligase (CRL4B) complex, is involved in regulating a variety of developmental and physiological processes including the skeletal development and stemness of cancer stem cells. However, nothing is known about the possible role of CUL4B in the osteogenic differentiation of PDLSCs. Here, we found that knockdown of CUL4B decreased the proliferation, migration, stemness and osteogenic differentiation ability of PDLSCs. Mechanistically, we demonstrate that CUL4B cooperates with the PRC2 complex to repress the expression of miR-320c and miR-372/373-3p, which results in the upregulation of RUNX2, a master transcription factor (TF) that regulates osteogenic differentiation. In brief, the present study reveals the role of CUL4B as a new regulator of osteogenic differentiation in PDLSCs.